2021
DOI: 10.35848/1347-4065/abe7fd
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical surface plasmon resonances on perpendicular magnetic thin films consisting of CoPt/ZnO/Ag stacked nanolayers

Abstract: Magneto-plasmonic phenomena on CoPt/ZnO/Ag stacked nanolayers were investigated in polar Kerr excitation geometry. The nanolayer displays an ideal square-shaped out-of-plane magnetic hysteresis loop with a large polar Kerr activity. The surface plasmon resonances (SPRs) induce drastic magneto-optical (MO) responses with a narrow linewidth and a sharp reversal of the Kerr polarity. The CoPt/ZnO/Ag nanolayer is a candidate for high-performance chemical sensor elements. For example, an MO‒SPR sensor with a Pd sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[26][27][28][29][30] The ultrahigh response is attributed to the strong local electric field on the surface of the Au/Co/Au film under the surface plasmon resonance (Figure 5). [31,32] The full width at half maxima (FWHM), a pivotal point to evaluate the sensing characteristic of the SPR sensor, of Au/Co/Au magnetic sensor with different thicknesses of Co layer (0, 6, 9, 12 nm) is 0, 8.8, 11.9, 12.4, and 12.6, respectively, which rises with the thickness of Co increase, due to the ohmic loss of Co. The Au/Co/Au sandwich structure, where the top and bottom Au layers are equivalent to a resonant cavity, can tremendously reduce Co's ohmic loss and improve sensitivity and quality factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30] The ultrahigh response is attributed to the strong local electric field on the surface of the Au/Co/Au film under the surface plasmon resonance (Figure 5). [31,32] The full width at half maxima (FWHM), a pivotal point to evaluate the sensing characteristic of the SPR sensor, of Au/Co/Au magnetic sensor with different thicknesses of Co layer (0, 6, 9, 12 nm) is 0, 8.8, 11.9, 12.4, and 12.6, respectively, which rises with the thickness of Co increase, due to the ohmic loss of Co. The Au/Co/Au sandwich structure, where the top and bottom Au layers are equivalent to a resonant cavity, can tremendously reduce Co's ohmic loss and improve sensitivity and quality factors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the high cost of the detection system and complex light path usually hinder practical application. [16] The optic fiber based on the SPR covered with magneto-fluid (a colloidal liquid consisting of magnetic solid particles, active agent, and medium) is sensitive to the temperature and magnetic field also, which realized two-parameter measurements simultaneously, although the magneto-fluid is unstable, restrained further development. [17] Previous reports on the detection of magnetic fields have suffered from issues such as sensitivity, response time, stability, and applicability.In this work, we demonstrate the modulation of magnetic fields on the interaction between light and matter and prepare an Au/Co/Au magneto-optic surface plasmon resonance (MOSPR) sensor by electron beam vapor deposition.…”
mentioning
confidence: 99%
“…Recently, we experimentally demonstrated the reversal of MO polarity and a large θ K of ± 21° in a polar MO‒SPR element comprising CoPt/Ag bilayers 28 . However, the upper limit of Kerr rotation (± 90°) is only possible in the Al 2 O 3 /CoPt/AZO trilayers.…”
Section: Resultsmentioning
confidence: 99%
“…Several theoretical and experimental studies have also shown that the SPRs significantly enhance polar Kerr activities 1 , 2 , 27 . We recently reported that SPR elements comprising perpendicular magnetic Co 80 Pt 20 /ZnO/Ag trilayers produce a giant polarization angle with narrow linewidth under polar Kerr excitation 28 . A new type of chemical sensor for detecting hydrogen gas was also demonstrated in the CoPt trilayers with an ideal square-shaped magnetic hysteresis loop.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that magnetoplasmonic sensors are being actively used for the detection of gases 194 and infectious diseases. 195 Additional areas where magnetoplasmonic sensors may find applications include material characterization.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%